2007
DOI: 10.3989/cyv.2007.v46.i6.218
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de la estabilidad de fase en SrZrO<sub>3</sub> en función de la temperatura de sinterización

Abstract: Estudios recientes sobre la transición de fase en SrZrO 3 haciendo uso entre otras técnicas de Difracción de Rayos X y de Neutrones, junto con espectroscopías de correlación angular o espectroscopía Raman, ponen de manifiesto que el diagrama de fases de estos compuestos no es simple, ni está claramente definido. Las temperaturas de transición proporcionadas, son fuertemente dependientes de la historia térmica del material. En este trabajo, presentamos por primera vez el estudio de la estabilidad de fase en fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The cu" are related to the energy splitting produced by the static quadruple interaction and satisfy cu 1 +cu 2 =(X»3. These frequencies depend on the quadruple frequency cüQ=e 2 Qy zz l[4I(2I-\)h\ and r¡. The a Ak are functions only of the asymmetry parameter.…”
Section: Pac Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The cu" are related to the energy splitting produced by the static quadruple interaction and satisfy cu 1 +cu 2 =(X»3. These frequencies depend on the quadruple frequency cüQ=e 2 Qy zz l[4I(2I-\)h\ and r¡. The a Ak are functions only of the asymmetry parameter.…”
Section: Pac Spectroscopymentioning
confidence: 99%
“…As the temperature decreases, these compounds exhibit phase transitions to structures of lower symmetry, and their phase diagrams are strongly dependent on the characteristics of the A, A', B and B' elements. In these phase transitions, the atomic displacements from their ideal positions in the cubic structure are relatively small [1][2][3][4][5][6]. It has been observed that these materials can contain oxygen vacancies [7].…”
Section: Introductionmentioning
confidence: 99%